Pemberdayaan Berbasis Kemitraan Antara Pemerintah dengan Kelompok Tani Tri Tunggal Wonorejo - Derry Ahmad Rizal (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2017)
This paper examines how the partnership was established between the Sleman Government and the peasant group of Tri Tunggal in Wonorejo—a policy appropriate partnership. It is known that the perceived policy sometimes turns things around with what is in the field or the right target regulations according to the needs of the community. This article is based on two theories, top-down policies and social capital as a form of organizing peasant groups. In answering the question, in fact, this article is an extension of the design of a qualitative research model that describes, analyzes, and interprets field data in a narrative way. For that, the method of interviewing, observation, and documentation is chosen to complete the data until it can be interpreted into the new meaning of science. Thus, this research has produced some interesting findings, such as government partnership to peasant group of Tri Tunggal with the approach of counseling, mentoring, and marketing of the agricultural product. As a matter of fact, the regulation is a reference for the government in empowering peasant groups.Tulisan ini mengkaji tentang bagaimana kemitraan yang dibangun antara Pemerintah Sleman dengan Kelompok Tani Tri Tunggal Wonorejo—kemitraan yang sesuai dengan kebijakan. Diketahui bahwa kebijakan yang dipersepsikan terkadang berbalik keadaan dengan apa yang ada di lapangan atau regulasi yang tepat sasaran sesuai kebutuhan masyarakat. Artikel ini didasari atas dua teori, kebijakan yang bersifat top down dan modal sosial sebagai bentuk pengorganisasian kelompok tani. Dalam menjawab persoalan tersebut, sebetulnya, artikel ini merupakan pengembangan dari desain model penelitian kualitatif yang menggambarkan, menganalisa, dan menginterpretasikan data lapangan secara naratif. Untuk itu, metode wawancara, observasi, dan dokumentasi dipilih untuk melengkapi data hingga dapat ditafsirkan ke dalam makna baru keilmuan. Dengan begitu, riset ini melahirkan beberapa temuan menarik, antara lain kemitraan yang dilakukan pemerintah kepada kelompok tani Tri Tunggal dengan pendekatan penyuluhan, pendampingan, dan pemasaran hasil produksi pertanian. Sebagai dasarnya, regulasi Perda menjadi acuan bagi pemerintah dalam memberdayakan kelompok tani.